Investigating the therapeutic utility of targeting the chemokine fractalkine and the suitability of Natural Killer cell therapy in Oesophageal Adenocarcinoma - Marion, Caroline Dalal (Trinity College Dublin. School of Medicine. Discipline of Surgery, 2025)
Oesophageal adenocarcinoma (OAC) arises in a background of chronic inflammation and is characterised by an aggressive phenotype and poor prognosis, with a five-year survival rate of less than 25%. Current response rates to chemotherapy and/or radiotherapy are only ~30% and most patients present with advanced-stage disease, underscoring the urgent need for a deeper understanding of mechanisms driving tumour progression and the identification of novel therapeutic strategies. Immunotherapy efficacy rates for OAC have also been disappointing so far, standing below 25%. It is well established that the immune infiltrate in solid tumours can be a strong prognostic factor in cancer patients and higher intratumoural frequencies of CD8+ T cells and natural killer (NK) cells are often associated with improved survival and better response to immunotherapy. Our group have shown that OAC patients with higher visceral obesity have the lowest numbers of intratumoural NK cells, contributing to `immune-excluded tumours in this poor prognosis malignancy. We have previously shown that the pro-inflammatory chemokine fractalkine plays a role in the disruption of anti-tumour immunity in OAC via the erroneous recruitment of NK and CD8+ T cells to the visceral adipose tissue (VAT), at the expense of effective tumour infiltration. Furthermore, we have reported that modulation of the fractalkine receptor CX3CR1 with the modulator E6130 can prevent NK cell migration towards the soluble chemotactic cues of the VAT and redirect them towards the tumour. Thus, we propose that E6130 holds potential alone and in combination with other immunotherapies to re-invigorate their infiltration and killing of OAC tumours. Other groups have reported the direct pro-tumourigenic effects of fractalkine in cancers of the stomach, lung, pancreatic and prostate and have demonstrated that targeting CX3CR1 can attenuate these effects. Therefore, this study aims to elucidate 1) the direct biological effects of fractalkine on OAC tumour progression and 2) the additional anti-tumour utility of E6130 in OAC, beyond NK cell migration. We propose that fractalkine may directly promote OAC tumour survival, progression and metastasis and that E6130, a CX3CR1 modulator, can attenuate such effects. Finally, this study evaluated the potential utility of KHYG-1 cell therapy in OAC, investigating whether they were susceptible to the chemotactic cues of the VAT and if this could be overcome using E6130. Our data demonstrate that fractalkine significantly increases OAC cell line survival, proliferation and migration and that E6130 can reverse these pro-tumourigenic effects. In addition, the data presented here demonstrate the utility of E6130 in treatment-resistant OAC tumour cell lines. The tumouricidal activity of E6130 was validated in ex vivo OAC patient tumour samples further highlighting the anti-cancer therapeutic potential of this drug in OAC. Moreover, our data uncovered associations between CX3CR1 expression in OAC tumour cells and stemness and metastatic potential suggesting that CX3CR1 expression confers a survival advantage and might hold prognostic utility. Our findings also show that E6130 elicits no detrimental effects on NK cell phenotype and function, further strengthening its therapeutic potential. Finally, this study revealed that while KHYG-1 cell therapy are from distinct blood-derived NK cells in phenotype, they exhibit similar preferential migration towards the VAT and this cannot be reduced using E6130. Interestingly, KHYG-1 migration towards OAC tumour can be enhanced by remodelling the TME with the chemokine IP-10. In conclusion, this study uncovers the pro-tumourigenic role of fractalkine and additional therapeutic potential of E6130 in OAC. Moreover, if E6130 was selected as a combination strategy with NK cell therapy, our data suggest that blood-derived NK cells would be more amenable to its effects than KHYG-1 cell therapy. Ultimately, this project uncovers novel data on the therapeutic utility of E6130 in OAC, which holds promise to promote tumour eradication via its reversal of fractalkines direct and indirect pro-tumourigenic effects.
APPROVED
Keywords: Chemokine; Fractalkine; Oesophageal Cancer; Immunology; NK cell therapy; NK cell